2020
DOI: 10.3390/ma13184160
|View full text |Cite
|
Sign up to set email alerts
|

Sound Transmission Loss of a Sandwich Plate with Adjustable Core Layer Thickness

Abstract: Compressible Constrained Layer Damping (CCLD) is a novel, semi-active, lightweight-compatible solution for vibration mitigation based on the well-known constrained layer damping principle. The sandwich-like CCLD set-up consists of a base structure, a constraining plate, and a compressible open-cell foam core in between, enabling the adjustment of the structure’s vibration behaviour by changing the core compression using different actuation pressures. The aim of the contribution is to show to what degree, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…This model should also be capable of predicting the characteristic sound insulation terms as described in Table 1. To accomplish this, the acoustic model should consider a 1/3rd octave frequency range between 100 Hz and 3150 Hz with sufficient accuracy in comparison with experimental test data [16,48].…”
Section: Emphasis Is Primarily Towards Low Noisementioning
confidence: 99%
“…This model should also be capable of predicting the characteristic sound insulation terms as described in Table 1. To accomplish this, the acoustic model should consider a 1/3rd octave frequency range between 100 Hz and 3150 Hz with sufficient accuracy in comparison with experimental test data [16,48].…”
Section: Emphasis Is Primarily Towards Low Noisementioning
confidence: 99%
“…These models should also be capable of predicting the characteristic sound insulation terms as described in Table 1. To do this, the acoustic model should consider a 1/3 rd octave frequency range between 100 Hz and 3150 Hz with sufficient accuracy in comparison with experimental test data [15,46]. This is the first study to characterize the acoustic insulation of plasterboard partitions featuring studs with the perforated web.…”
Section: Introductionmentioning
confidence: 99%
“…Junctions and boundary conditions proved to significantly affect the results, pointing out the importance of a proper design and modeling of such devices. Finally, Ehrig et al [ 12 ] investigated the potential of compressible constrained layer damping (CCLD) that is a semi-active, lightweight-compatible solution for vibration mitigation based on a base structure, a constraining plate, and a compressible open-cell foam core in between, enabling the adjustment of the structure’s vibration behavior by changing the core compression using different actuation pressures. The results showed that such changes affected transmission loss in the range between 1 kHz and 5 kHz, with the best performance appearing when maximum compression was applied.…”
mentioning
confidence: 99%